An Assessment of a Major Global Full-Service Network Airline’s Waste Management: A Case Study of Korean Air - Baxter, Glenn (International Journal of Environment, Agriculture and Biotechnology, 2022)
Using an in-depth longitudinal research approach, this study has examined how Korean Air, a major global full-service network airline, manages its wastes in an environmentally sustainable manner. The study period was from 2007 to 2021. Korean Air has defined and implemented a “Green” Management Policy that underpins its sustainability goals. The airline’s waste management is underpinned by the 3Rs Waste Management Framework. Korean Air aims to reduce wastes wherever possible. Where this is not possible then the airline aims to re-use its wastes. Wastes that are unsuitable for re-use are recycled when their characteristics are suitable for such an approach. Wastes that cannot be re-used, recycled, or incinerated are disposed to landfill. The airline’s cabin wastes are disinfected and incinerated in accordance with the relevant regulations. Wastes generated by Korean Air can be broadly split into domestic waste generated from transportation services and designated or hazardous waste generated from aircraft maintenance. The case study found that there was an overall upward trend in Korean Air’s annual recycled wastes from 2010 to 2019. The airline’s incinerated wastes exhibited a general upward trend from 2007 to 2019. Koreans Air’s annual wastes disposed to landfill displayed a general downward trend during the study period. Koreans Air’s annual wastes were influenced by the reduced passenger traffic and flight operations due to the COVID-19 pandemic in 2020 and 2021. The COVID-19 pandemic has had a profound impact on the global aviation industry and has the global pandemic resulted in a downturn in passenger traffic and flight operations.